Gallbladder large cell neuroendocrine carcinoma in a patient with multiple myeloma: a case report and literature review - Yin, Yuhan; Dai, Xinjie; Li, Dan; Yang, Xinyu; Ming, Nan; Xiang, Kang; Wu, Dengding; Ai, Kong; Yao, Rucheng; Hu, Jun (Frontiers in Oncology, 2025)
Gallbladder Large Cell Neuroendocrine Carcinoma (GB-LCNEC), an extremely rare pathological subtype of gallbladder malignancies, is characterized by high aggressiveness and insidious onset, often leading to poor prognosis and presenting significant clinical management challenges. This report presents the complete treatment course of a patient diagnosed with GB-LCNEC complicated by active Multiple Myeloma (MM), accompanied by a systematic review of relevant literature published over the past decade. Preoperative imaging revealed a gallbladder mass, which was pathologically confirmed postoperatively as GB-LCNEC through histological and immunohistochemical analysis. The tumor demonstrated large cell morphology, high mitotic activity (Ki-67 index of 50%), and strong expression of neuroendocrine markers, including Insulinoma-Associated Protein 1 (INSM1). Despite the concurrent diagnosis of active MM, a Multidisciplinary Team (MDT) successfully performed radical resection for gallbladder carcinoma, which included cholecystectomy, wedge resection of adjacent hepatic tissue, and regional lymphadenectomy at the hepatic hilum. An R0 resection was achieved, laying a solid foundation for postoperative management. Given the patient’s limited tolerance to the standard Etoposide–Cisplatin (EP) chemotherapy regimen, a milder, individualized approach using the Capecitabine–Temozolomide (CAPTEM) regimen was selected. Simultaneously, the patient’s MM was treated with the Daratumumab–Lenalidomide–Dexamethasone (DRD) regimen. At six-month follow-up, there was no evidence of recurrence or metastasis, and the patient maintained a favorable general condition. This case underscores that in highly aggressive malignancies such as GB-LCNEC, surgical resection remains a cornerstone of effective disease control and survival extension, even in the presence of severe comorbidities. MDT-based decision-making and personalized treatment strategies are essential for optimizing therapeutic outcomes and minimizing treatment-related risks. Future research should prioritize the development of multicenter clinical registries and large-scale molecular profiling, while also evaluating emerging modalities such as targeted therapies and immunotherapy to ultimately improve the prognosis of this rare tumor entity.